2014
DOI: 10.1007/s00198-014-2698-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of hip fracture prevention with vitamin D supplementation: a Markov micro-simulation model applied to the French population over 65 years old without previous hip fracture

Abstract: Population screening for vitamin D insufficiency followed by treatment based on the vitamin D serum level is the most cost-effective strategy for preventing hip fracture occurrence in the population over 65 years old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 35 publications
0
45
0
Order By: Relevance
“…These data are consistent with cost-effectiveness assessments of universal vitamin D supplementation in older adults in the USA 9 and also in Western European populations but using fractures as the primary modifiable outcome. 10 11 …”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with cost-effectiveness assessments of universal vitamin D supplementation in older adults in the USA 9 and also in Western European populations but using fractures as the primary modifiable outcome. 10 11 …”
Section: Discussionmentioning
confidence: 99%
“…The identified studies spanned a period of 20 years, with the earliest being published in 1995 and the majority emerging between 2012 and 2016. Studies were carried out in the UK (15)(16)(17)(18)(19), the USA (20,21), Australia (22,23), France (24), Finland (25), Sweden (26) and Germany (27). Additionally, there was one multi-country study that carried out cost-effectiveness analyses in seven European countries (28).…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Additionally, there was one multi-country study that carried out cost-effectiveness analyses in seven European countries (28). The majority of studies (n=7) evaluated supplementation strategies of vitamin D alone in the adult population (16,17,20,21,(23)(24)(25). Other studies investigated calcium and vitamin D interventions either through oral supplements (n=4) (15,22,26,28) or food fortification (n=1) (27).…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 8 Additionally, studies have shown that calcium and vitamin D supplementation is a cost-effective method of preventing future fragility fractures in patients who have sustained a hip fracture. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%